Psychological factors of starting entrepreneurs’ business success - Yurchynska, Hanna; Serdiuk, Oleksandr (Social Welfare: Interdisciplinary Approach, 2017)
The article presents the results of the performed research of personal psychological factors contributing to business success. The analysis of these factors was carried out according to three criteria of business success: entrepreneurial motives, entrepreneurial goals, and entrepreneurial resources. The differences in entrepreneurial motives and goals of successful entrepreneurs and beginners have been determined. The revealed personal traits promoting business success are autonomy, self-expression, purposefulness, planning, and self-efficacy.
Keywords: business success; entrepreneurial motives; entrepreneurial goals; entrepreneurial resources; personal traits of an entrepreneur